Ethnicity Differences in Uses and Management Practices of Bitter Kola Trees (Garcinia kola) in Cameroon - Yogom, B.T.; Avana-Tientcheu, M.L.; Mboujda, M.F.M.; Momo, S.T.; Fonkou, T.; Tsobeng, A.; Barnaud, Adéline; Duminil, J. (Springer, 2020)
Bitter kola (Garcinia kola) is an indigenous multipurpose tree species in West and Central Africa, threatened by overexploitation and classified by the IUCN as vulnerable. Understanding local knowledge and management patterns in different socioecological contexts could contribute to designing strategies for conservation and long-term use of the species. In order to characterize the parts of the plant and the harvesting techniques that are used by different ethnic groups in Cameroon, we conducted surveys through the use of semi-structured questionnaires (N = 182) in six different sites covering different agro-ecological zones where the species is present (forest and savanna). Ethnic groups from the savanna agro-ecological zone shared similar patterns in G. kola organs/parts used and harvesting techniques, but these patterns differed among ethnic groups from the savanna and forest zones and within the forest zone. Ethnic groups from the savanna zone mainly harvest the species for its seeds that are used as stimulants. Conversely ethnic groups from the forest zone mainly collect bark and roots, and uses differ between agriculturalists (Fang and Bassa) and hunter-gatherers (Baka). These patterns have direct consequences on species management practices. Savanna farmers applied sustainable harvesting as they extract fruits and seeds and planting more trees in order to increase the species’ contribution to their livelihood. People in the forest zone destructively felled standing trees, threatening the species in its natural environment. The influence of these results on the conservation status of the species in the region are discussed.